2021
DOI: 10.21203/rs.3.rs-607400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological interventions of virtual gamification as a motivational basis: A mixed-method systematic review

Abstract: BACKGROUNDStudents constantly seek ways to improve productivity within academia. With the advancement of technology in the recent decade, virtual implementations may provide additional support for student productivity, particularly during the COVID-19 pandemic with online learning. One of the virtual realms for motivation include gamification, which has potential as an effective tool to further bolster an individual’s source of intrinsic motivation.METHODUsing a convergent integrated synthesis approach, qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…It gives students more authority over their academic assignments, improving their appearance and encouraging teamwork, diligence, and other admirable traits (Manzano-León et al, 2021). Students' behavior and attitudes toward learning have been shown to change because of gamification, which also increases motivation and engagement and fosters an environment that is conducive to learning (Xu et al, 2021).…”
Section: Gamification In Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…It gives students more authority over their academic assignments, improving their appearance and encouraging teamwork, diligence, and other admirable traits (Manzano-León et al, 2021). Students' behavior and attitudes toward learning have been shown to change because of gamification, which also increases motivation and engagement and fosters an environment that is conducive to learning (Xu et al, 2021).…”
Section: Gamification In Educationmentioning
confidence: 99%
“…Gamification in educational settings has been shown to have a positive impact on student engagement, motivation, and academic performance, which can be closely tied to students' goal orientation. Research indicates that when gamification elements are introduced into the learning environment, they can enhance students' intrinsic motivation and encourage them to focus on mastery and learning goals rather than solely on performance metrics (Chen et al, 2018;Moreira et al, 2020;Xu et al, 2021). For instance, studies have found that gamified activities can lead to superior academic performance in subjects like statistics and math, as students exposed to gamification showed increased confidence in their competencies and were more motivated to learn (Fuster-Guilló et al, 2019;Manzano-León et al, 2021).…”
Section: Gamification and Students' Goal Orientation In Improving Aca...mentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic literature review by Joy et al also indicates that seven out of 10 support the idea that gamification could raise the user's intrinsic motivation. The remaining three are not relevant to the research topic [8].…”
Section: Gamification and Intrinsic Motivationmentioning
confidence: 99%